Hypoglycaemic Effect of The Aqueous Extract of The Leaves of Allanblackia floribunda Oliv. (Guttiferae) - Funmileyi O. Awobajo, Ibiyemi I. Olatunji-Bello, Toluwalope O. Odugbemi, Gloria A. Ayoola, Ifeoma E. Ngene (Journal of Phytology, 2010)
Background: Diabetes mellitus continues to present a major medical challenge despite the array of antidiabetic medicines on the market. The disorder is characterized by chronic hyperglycaemia and glycosuria. This study aims to study the hypoglycaemic potential of the aqueous extract of Allanblackia floribunda leaves in alloxan-induced diabetic rats.Ã‚Â Methods: In the study, 25 albino rats weighing between 180-200 g were divided into five groups of five animals each. Group 1 contained normal untreated rats, group 2 contained diabetic untreated rats, group 3 & 4 were diabetic rats treated with 50 and 25 mg/kg of theÃ‚Â aqueous extract of A. floribunda leaves respectively and group 5 contained diabetic rats treated with 0.5mg/kg glibenclamide for 15 days. Animals for the hypoglycaemic study were treated for two weeks post induction. Fasting blood glucose (FBG) levels were determined using the glucose oxidase method. FBG of the experimental animals were significantly reduced by A. floribunda. Results: A 72.5%Ã‚Â and 62.8% reduction in glucose level was observed for 50 mg/kgÃ‚Â and 25 mg/kg dose of A. floribunda while a 71.8% reduction was noted for 0.5 mg/kg glibenclamide. Hence, 50 mg/kg dose of the aqueous extract was as potent as 0.5 mg/kg glibenclamide in inducing hypoglycaemia. Pre-treatment of the animals with the extracts for two weeks resulted in a significant lowering of the fasting blood glucose level of the animals pre-incubation and significantly reduced the effect of alloxan on FBG levels of the animals. Phytochemical screening of the aqueous leaf extract revealed the presence of tannins, flavonoids, terpenoids, saponins, cardiac glycosides, alkaloids, steroids and anthraquinones. Conclusion: This study has demonstrated the potential of the aqueous extract of A. floribunda as both a hypoglycaemic agent and suggests that the extract may have a protective effect against the development ofÃ‚Â diabetes.